A Dense Dipole Array for mid-frequency aperture arrays - Gilmore, J.; Davidson, David; Noordam, J. (2015)
© 2015 IEEE. This paper presents preliminary results of a Dense Dipole Array (DDA) design. The array consists of tightly coupled dipole elements above a ground plane and fed differentially through a specially designed common-mode suppressing feed. Measurements of a 4 × 4 prototype indicate an impedance bandwidth of ˜ 2:5 : 1.